Cardiac 123I-MIBG uptake in de novo Brazilian patients with Parkinson's disease without clinically defined dysautonomia - Marco Antonio Araujo Leite; Osvaldo J. M. Nascimento; João Santos Pereira; Clayton Amaral; Cláudio T. Mesquita; Jader C. Azevedo; Adriana S. X. de Brito; Felipe Villela Pedras (Arquivos de Neuro-Psiquiatria)
Myocardial scintigraphy with meta-iodo-benzyl-guanidine (123I cMIBG) has been studied in Parkinson's disease (PD), especially in Asian countries, but not in Latin America. Most of these studies include individuals with PD associated to a defined dysautonomia. Our goal is to report the cardiac sympathetic neurotransmission in de novo Brazilian patients with sporadic PD, without clinically defined dysautonomia. We evaluated retrospectively a series of 21 consecutive cases with PD without symptoms or signs of dysautonomia assessed by the standard bedside tests. This number was reduced to 14 with the application of exclusion criteria. 123I cMIBG SPECT up-take was low or absent in all of them and the heart/mediastinum ratio was low in 12 of 14. We concluded that 123I cMIBG has been able to identify cardiac sympathetic neurotransmission disorder in Brazilian de novo PD patients without clinically defined dysautonomia.